2007
DOI: 10.1182/blood-2006-06-029173
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-independent growth and clonal expansion of a primary human CD8+ T-cell clone following retroviral transduction with the IL-15 gene

Abstract: Malignancies arising from retrovirally transduced hematopoietic stem cells have been reported in animal models and human gene therapy trials. Whether mature lymphocytes are susceptible to insertional mutagenesis is unknown. We have characterized a primary human CD8 ؉ Tcell clone, which exhibited logarithmic ex vivo growth in the absence of exogenous cytokine support for more than 1 year after transduction with a murine leukemia virus-based vector encoding the T-cell growth factor IL-15. Phenotypically, the clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 55 publications
2
59
1
Order By: Relevance
“…It is worth noting that IL-15 has been shown to be important for CTL activation and generation of long-lived CD8ϩ memory cells (24,25). Both the CD8ϩ cells in the IL15 transgenic mice (26) and the IL15 transduced primary human CD8ϩ cells (27) indeed showed similar phenotypes as leukemic T-LGL. However, IL-15 alone cannot fully inhibit the onset of apoptosis in our model (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…It is worth noting that IL-15 has been shown to be important for CTL activation and generation of long-lived CD8ϩ memory cells (24,25). Both the CD8ϩ cells in the IL15 transgenic mice (26) and the IL15 transduced primary human CD8ϩ cells (27) indeed showed similar phenotypes as leukemic T-LGL. However, IL-15 alone cannot fully inhibit the onset of apoptosis in our model (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Induces Apoptosis 107,108 Telomerase activation 122 Unconfirmed Unconfirmed IL- 15 Decrease apoptosis 136 Decrease apoptosis 130,131 Unconfirmed Telomerase activation [123][124][125] Decrease apoptosis 132 engineering of cells described here, that can be regulated by transfection with suicide genes such as those for herpes simplex virus thymidine kinase (TK) 140 or CD20 141 or the use of transfected extracellular FK506 binding domains with Caspase-9 signaling motifs to cause cell death upon treatment with FK506. 142 …”
Section: Il-21mentioning
confidence: 80%
“…122 Considering CD8 C T cells, IL-15 has been shown to increase CD8 C memory T cell longevity by inducing telomerase activity through JAK3 and PI3K signaling pathways. 123,124 A further study, looking at both IL-7 and IL-15 showed an upregulation of na€ ıve CD8 C T cells when incubated with these cytokines, with a higher response seen with IL-15. 125 Stimulation of telomerase activity in immune cells makes these cytokines potentially harmful to administer in cancers such as leukemia, where there is already uncontrolled telomerase activity occurring in T cells.…”
Section: Underlying Mechanisms That Increase Immune Cell Longevitymentioning
confidence: 97%
“…Addition of transgenes encoding IL-2, IL-7, IL-15 or IL-21 has been studied in an effort to improve the effector function, persistence or in vivo efficacy of CAR-modified T cells [43]; however, the finding of persistent autonomous proliferation of a CD8 ? T cell clone transduced to express IL-15 suggests that caution is warranted in translation of this approach [44]. A similar approach, which involves introduction of a transgene encoding IL-12 with the CAR construct, has been investigated as a strategy to overcome the suppressive effects of regulatory CD4 ?…”
Section: Design Of Chimeric Antigen Receptorsmentioning
confidence: 99%